EXPERIMENTAL STUDY ABOUT CHECK VALVE IN NEUROLOGICAL APPLICATION - Bim, Camila [UNESP]; Vieira, Edson Del Rio [UNESP]; Mansur, Sergio Said [UNESP]; Barbosa, Marcos Pinotti; Camilo Pinto, Jose Ricardo; Maset, Angelo Luis (Inegi-inst Engenharia Mecanica E Gestao Industrial, 2012)
In the present work is proposed the experimental study of hydrodynamic behaviour of membrane neurological valve, applied in treatment of hydrocephalus, a pathophisiology that affects both adults and children, caused due to the excess of cerebrospinal fluid in brain ventricles.